Comparison of epinephrine and felypressin pressure effects in 1K1C hypertensive rats treated or not with atenolol - Fleury, Camila A.; Andreo, Vagner C.; Lomba, Pedro C.; Dionísio, Thiago J.; Cardoso, Sandra Lia do Amaral [UNESP]; Santos, Carlos F.; Faria, Flávio A. (Springer Nature, 2015)
Epinephrine is considered the gold standard vasoconstrictor for hypertensive patients, but few studies report felypressin’s effects. The present study aimed to analyze and compare the effects of these two vasoconstrictors, injected by the intravenous route, on the arterial pressure of normotensive, hypertensive and atenolol-treated hypertensive rats. Method The hypertension model was one-kidney-one-clip (1K1C): the main left renal artery was partially constricted and the right kidney was surgically removed in 45-day-old male Wistar rats. 1K1C hypertensive rats received atenolol (90 mg/kg/day) by gavage for 2 weeks. 28–35 days after hypertension induction, a catheter was inserted into the left carotid artery to record direct blood pressure values. The following parameters were recorded: minimal hypotensive response, maximal hypertensive response, response duration and heart rate. Results Epinephrine, but not felypressin, exerted an important hypotensive action; non-treated hypertensive rats showed more pronounced vasodilation. Treated and non-treated rats showed hypertensive responses of the same magnitudes in all groups; 1K1C atenolol rats showed reduced hypertensive responses to both vasoconstrictors. Felypressin’s response duration was longer than that of epinephrine in all groups. Epinephrine increased heart rate while felypressin reduced this parameter only in the normotensive group. Conclusions Our results suggest that felypressin has equipotent pressure responses when compared with epinephrine, showing a greater extent of action. Atenolol’s reduction of hypertensive effects surprisingly suggests that atenolol β-blockade may also be important for felypressin’s cardiovascular effect, as is widely known for epinephrine. Our data suggest that felypressin is safe for hypertensive subjects, in particular those receiving atenolol.